Effects of Sewage Sludge at different pH Levels on Ipomoea Aquatica (Bangladesh Journal of Scientific and Industrial Research, 2012)
An experiment was conducted to study the effects of sewage sludge on the response of Ipomoea aquatica to plant nutrients and heavy metals  in soil at different soil pH. An incubation study was done for the selection of four individual pH levels, viz., 4.7, 5.7, 6.6 and 7.8 to be  used for the plant culture experiment. Yield of Ipomoea aquatica and concentration and uptake of N, P, K, Ca, Mg, Cd, Cu, Fe, Mn and Zn  in the plant were evaluated. Application of sewage sludge in soil increased the concentration and uptake of the elements in Ipomoea. Slightly  acidic to slightly alkaline pH was found to be better for amendment of soil with sewage sludgeDOI: http://dx.doi.org/10.3329/bjsir.v47i1.10721 Bangladesh J. Sci. Ind. Res. 47(1), 47-54, 2012